2003
DOI: 10.1111/j.1745-3992.2003.tb00142.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Improving Teachers' Classroom Assessment Decision Making: Implications for Theory and Practice

Abstract: Teacher assessment decision making is described a s a process that may be important in developing a measurement theory for classroom assessment. Teacher beliefs and values about what and how to assess often conflict with the pressures of external demands, especially recent high-stakes large-scale testing. With this sense of tension, teachers make assessment decisions that will engage and motivate students and enhance learning. Implications f o r a measurement theory of classroom assessment, as well a s teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
118
1
20

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(145 citation statements)
references
References 24 publications
(31 reference statements)
6
118
1
20
Order By: Relevance
“…Although group and team work is strongly recommended in teaching and learning theories, it is less so in current measurement theory. Third, many of the issues identified in the initial cycle related to what is called 'academic enablers' such as effort and student participation (Duncan and Noonan, 2007;McMillan, 2003), or student predisposition, ISSN 1948-5476 2010 www.macrothink.org/xxx 7 such as submitting late assignments (Marzano, 2000). These seem to have been replaced in the final cycles by a greater number of references to measurement principles such as reliability, validity and fairness.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although group and team work is strongly recommended in teaching and learning theories, it is less so in current measurement theory. Third, many of the issues identified in the initial cycle related to what is called 'academic enablers' such as effort and student participation (Duncan and Noonan, 2007;McMillan, 2003), or student predisposition, ISSN 1948-5476 2010 www.macrothink.org/xxx 7 such as submitting late assignments (Marzano, 2000). These seem to have been replaced in the final cycles by a greater number of references to measurement principles such as reliability, validity and fairness.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…McMillan (2003) and Saxe et al (1999) found that experienced teachers are affected by previous knowledge, beliefs, values, expectations, emotions, and identity. They are also pressed by external influences such as curriculum related documents, policies, ISSN 1948-5476 2010 professional development programs, large-scale assessments (institutional impacts), and stakeholders such as colleagues, administration, students, and parents.…”
Section: Conclusion Limitations and Implications For Future Researchmentioning
confidence: 99%
“…Realizada mediante la aplicación de una pauta de cotejo especialmente diseñada (validada por criterio de jueces) y que consideró tres criterios de evaluación: Inicio, Desarrollo y Cierre de una clase, con un total de 13 indicadores de logro, demostrados útiles por la literatura [7][8][9][10][11] . La pauta de observación de clases fue aplicada por dos tipos de evaluadores: a) evaluadores pares (LS y CW) obteniendo 144 registros evaluados y b) estudiantes que respondieron 1.524 encuestas.…”
Section: Calidad De La Conducción De Clasesunclassified
“…Other teachers see assessment as formative as synonymous with development, learning, knowledge, adjustment and improvement. The divergence of perspectives is associated with the lack of clear institutional policy on assessment practices and previous experiences of the university teachers (Fletcher et al, 2012;McMillan, 2003). As a result, research is needed about how conceptions of assessment can be influenced and enhanced the institutional policy (Rust, 2007;Brown, 2004).…”
Section: Discussionmentioning
confidence: 99%